Examination management systems: A survey of user acceptance level in UiTM cawangan Pulau Pinang / Jamal Othman ... [et al.] - Othman, Jamal; Kadar, Rozita; Abdul Wahab, Naemah; Warris, Saiful Nizam (UiTM Cawangan Perlis, 2018)
Examination Management Systems (EMS) is a comprehensive system developed using JAVA programming language for data processing and Microsoft Access for reporting purposes. This system has been used and implemented at several campuses including Universiti Teknologi MARA Cawangan Pulau Pinang, Permatang Pauh Campus. The core objective of this system is to improve the efficiency and reducing the operational risks. A survey has been conducted to examine the user acceptance level of UiTM Cawangan Pulau Pinang since implemented in 2014. Questionnaires have been distributed to chief invigilators at every session of examination for 10 semesters and results of analysis are reported and concluded.